2021
DOI: 10.1101/2021.07.09.451843
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for tunable control of actin dynamics by myosin-15 in mechanosensory stereocilia

Abstract: SummaryThe motor protein myosin-15 is necessary for the development and maintenance of mechanosensory stereocilia, and myosin-15 mutations cause profound deafness. In a companion study, we report that myosin-15 nucleates actin filament (“F-actin”) assembly and identify a progressive hearing loss mutation (p.D1647G, “jordan”) which disrupts stereocilia elongation by inhibiting actin polymerization. Here, we present cryo-EM structures of myosin-15 bound to F-actin, providing a framework for interpreting deafness… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 89 publications
(137 reference statements)
3
29
0
Order By: Relevance
“…The coordination of Mg 2+ -ADP in our structure closely resembles the ones reported for the strong-ADP state of myosin-IB ( Mentes et al, 2018 ), myosin-VI ( Gurel et al, 2017 ), and myosin-XV ( Gong et al, 2021 ; Figure 1—figure supplement 4 ). Only the position of switch I differs appreciably between myosins, ultimately resulting in varying positions of the coordinated Mg 2+ ion.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…The coordination of Mg 2+ -ADP in our structure closely resembles the ones reported for the strong-ADP state of myosin-IB ( Mentes et al, 2018 ), myosin-VI ( Gurel et al, 2017 ), and myosin-XV ( Gong et al, 2021 ; Figure 1—figure supplement 4 ). Only the position of switch I differs appreciably between myosins, ultimately resulting in varying positions of the coordinated Mg 2+ ion.…”
Section: Resultssupporting
confidence: 83%
“… Comparison of the active sites of myosin-V in the strong-ADP state (orange) with the ones of ( A ) myosin-IB (PDB: 6C1D; Mentes et al, 2018 ), ( B ) myosin-VI (PDB: 6BNQ, nucleotide not modeled; Gurel et al, 2017 ), and ( C ) myosin-XV (PDB: 7R91, Gong et al, 2021 ) in the same state (shades of blue, shown as transparent). The coordination of Mg 2+ -ADP is almost identical in all four atomic models.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations